GAYA KEPEMIMPINAN, KOMUNIKASI, DAN PENGAMBILAN KEPUTUSAN DALAM MENINGKATKAN EFEKTIVITAS MANAJEMEN PADA LEMBAGA PENDIDIKAN ISLAM - Irma Rosita (Fakultas Tarbiyah IAI Almuslim Aceh, 2024)
This study aims to analyze the role of leadership style, communication, and decision-making in enhancing managerial effectiveness in Islamic educational institutions. Effective leadership in Islamic educational institutions requires a combination of adaptive and innovative leadership skills to direct organizational resources toward desired goals. Good communication between leaders, educators, and students plays a key role in creating a conducive and productive learning environment. Additionally, accurate, participatory, and data-driven decision-making ensures that policies align with the institution's and stakeholders' needs. The findings indicate that transformational and participative leadership styles are more effective in fostering motivation and trust among organizational members. Open and transparent communication supports the realization of good coordination among organizational elements, thereby minimizing conflicts and increasing operational efficiency. Decision-making processes involving various stakeholders enhance policy legitimacy and satisfaction among members. Islamic educational institutions are required to develop dynamic and long-term vision-oriented leadership patterns to address the challenges of globalization and educational modernization. With the support of effective communication and inclusive decision-making processes, managerial effectiveness can be improved, ultimately positively impacting educational quality. This study recommends that Islamic educational institutions focus more on enhancing leadership capacity, implementing communication technologies, and developing more participatory decision-making mechanisms. These efforts are essential for supporting more professional and adaptive institutional management in responding to change.